Colored Music in America: a Colored Sense of Belonging? A cultural-linguistic study of hip-hop music lyrics - Alouane, Nesrine (International Journal of Linguistics and Translation Studies, 2023)
As all people and nations experience a state of flux, national culture loses its solidity in the context of a global unified culture to which we are called, or rather forced, to belong. Here arise such vital questions as identity and belonging. The case study of this paper concerns the African-American sample as a minority group striving to seize its proper status in a ruthless West. This struggle comes highly significant when treading the edge of popular culture. The research is an inquiry into the extent to which belonging is felt, expressed and staged by the community in question throughout their representative popular culture, to mention hip-hop music. The complex nature of the topic requires, in fact, a multidisciplinary approach that encompasses, first, an anthropological examination of the backgrounds of the African-American ethnical group; second, a linguistic investigation of the African-American musical discourse (hip-hop lyrics); and third, a critical analytic deduction of the activist mission played by such musical genre concerning questions of identity and belonging. Practically speaking, the linguistic part will analyse a selected corpus of hip-hop song lyrics. The methodological process will use a qualitative content analysis technique to extract the linguistic patterns reinforcing the scope of identity and belonging. The concluding part will state some limitations that the research had encountered.